Cancer screening recommendations for individuals with Li-Fraumeni syndrome - Kratz, Christian Peter; Pajtler, Kristian Wilfried; Pfister, Stefan (Clinical cancer research, 2017)
Li-Fraumeni syndrome (LFS) is an autosomal dominantly inherited condition caused by germline mutations of the TP53 tumor suppressor gene encoding p53, a transcription factor triggered as a protective cellular mechanism against different stressors. Loss of p53 function renders affected individuals highly susceptible to a broad range of solid and hematologic cancers. It has recently become evident that children and adults with LFS benefit from intensive surveillance aimed at early tumor detection. In October 2016, the American Association for Cancer Research held a meeting of international LFS experts to evaluate the current knowledge on LFS and propose consensus surveillance recommendations. Herein, we briefly summarize clinical and genetic aspects of this aggressive cancer predisposition syndrome. In addition, the expert panel concludes that there are sufficient existing data to recommend that all patients with LFS be offered cancer surveillance as soon as the clinical or molecular LFS diagnosis is established. Specifically, the panel recommends adoption of a modified version of the “Toronto protocol” that includes a combination of physical exams, blood tests, and imaging. The panel also recommends that further research be promoted to explore the feasibility and effectiveness of these risk-adapted surveillance and cancer prevention strategies while addressing the psychosocial needs of individuals and families with LFS. Clin Cancer Res; 23(11); e38-e45. ©2017 AACR. See all articles in the online-only CCR Pediatric Oncology Series.
Gesehen am 15.11.2018